2018
DOI: 10.1002/slct.201702378
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Protocol for the Synthesis of 3‐Acyl Benzothiadiazine 1,1‐Dioxides

Abstract: A metal-free and efficient tandem synthesis of 3-acyl 3,4-dihydro-2H-1,2,4-benzothiadiazine-1,1-dioxides and 3-acyl-2H-1,2,4-benzothiadiazine-1,1-dioxides has been developed via CÀH functionalization of ethynylarenes and ethenylarenes followed by condensation with 2-aminobenzenesulfonamide. The reaction involves the formation of arylglyoxal as an intermediate from multiform substrates through Kornblum oxidation in the presence of iodine and DMSO. Use of simple and readily available starting materials, inexpens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[756,757] Sathe and group used a one-pot synthetic method where they stirred phenyl acetylene and styrene as model substrates with molecular iodine dissolved in DMSO at 110 °C for 1.0 hour in a sealed tube. [758] They have then . This group found that increasing the amounts of molecular iodine could increase the product yields.…”
Section: Carbon Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…[756,757] Sathe and group used a one-pot synthetic method where they stirred phenyl acetylene and styrene as model substrates with molecular iodine dissolved in DMSO at 110 °C for 1.0 hour in a sealed tube. [758] They have then . This group found that increasing the amounts of molecular iodine could increase the product yields.…”
Section: Carbon Insertionmentioning
confidence: 99%
“…Some of the synthetic routes for benzothiadiazine, involve the use of metal catalysts such as copper (Scheme 75 (a) and (b)) [756,757] . Sathe and group used a one‐pot synthetic method where they stirred phenyl acetylene and styrene as model substrates with molecular iodine dissolved in DMSO at 110 °C for 1.0 hour in a sealed tube [758] . They have then added 2‐aminobenzenesulfonamide to the reaction mixture, which lead to the formation of (1,1‐dioxido‐3,4‐dihydro‐2 H ‐benzo[e][1,2,4]thiadiazin–3‐yl)(phenyl)methanone when the reaction mixture was kept at room temperature for another 1.0 hour (Scheme 75 (c)).…”
Section: Carbon Insertionmentioning
confidence: 99%
“…A new, metal-free, efficient, and scalable approach was devised for the production of 3-acyl-3,4-dihydro-2 H -1,2,4-benzothiadiazine-1,1-dioxides 44 and 3-acyl-2 H -1,2,4-benzothiadiazine-1,1-dioxide 45 ( Scheme 25 ). In their study, Chaskar et al 71 employed affordable ethynyl arenes 1 and ethenyl arenes 27, which are readily accessible, as starting materials. These compounds consist of sp 2 and sp 3 carbon–hydrogen (C–H) bonds, respectively.…”
Section: Six-membered Ring Formation With Three-heteroatomsmentioning
confidence: 99%